Energy Independency and Sustainable Development in International Relations Context - Tiara Scoorpy Ananda Putra, Nyphadear; Satria, Randhi (Department of International Relations Universitas Pertamina, 2024)
Energy independence and sustainable development are critical issues in international relations. As the world population grows and industrialization and urbanization continue, there is a surge in energy demand. At the same time, environmental concerns and limited natural resources have made sustainable energy systems a pressing issue. Achieving energy independence and sustainable development is a crucial policy objective for many countries. Energy independence aims to reduce dependence on foreign energy sources and ensure energy supply security, while sustainable development aims to meet current energy needs without compromising the ability of future generations to meet their own. International cooperation is essential to achieving energy independence and sustainable development. Countries need to work together to ensure a stable and secure global energy supply while also reducing carbon emissions. Renewable energy sources such as wind, solar, hydro, and geothermal power have enormous potential to promote both energy independence and sustainable development.Energy independence and sustainable development are essential components of the global energy transition. By promoting renewable energy sources, developing new technologies, and cooperating internationally, governments and organizations can ensure a stable and secure global energy supply while reducing carbon emissions and promoting sustainable development.